Sprogvidenskab og virksomhedskommunikation - Andersen, Flemming Smedegaard (HERMES - Journal of Language and Communication in Business, 2005)
In recent years, the humanities and particularly linguistics have gained an increasing inﬂuence within the ﬁeld of business communication. Business communication has traditionally been seen as a discipline within the social sciences, and for instance copy writing has conventionally been an issue for advertising agencies or advertising departments, not an area for academic research. In this article I shall demonstrate how a linguistic theory as Systemic Functional Linguistics is developing within the studies of business communication at the University of Southern Denmark in Odense. I shall argue why Systemic Functional Linguistics is useful for business communication in general, and how Systemic Functional Linguistics can be used not only for copy writing but also for communication analysis, organizational culture analysis and communication and campaign planning.